Avoiding dangerous climate: results from the AVOID2 programme. (8th November 2017) - Lowe, J. A.; Arnell, N. W.; Warren, R.; Gambhir, A. J.; Bernie, D.; Thompson, E.
Abstract : The AVOID2 programme provided evidence for UK Government on what might constitute dangerous climate change and the feasibility of avoiding it. The programme quantified some of the benefits of moving from a world that warms by around 4–5°C to one limiting global warming to below or well below 2°C. Whilst there is evidence that this transition is feasible, it will require early action to reduce emissions and to develop the potential for large‐scale deployment of a range of low carbon technologies. Abstract : The AVOID2 programme provided evidence for UK Government on what might constitute dangerous climate change and the feasibility of avoiding it. The programme quantified some of the benefits of moving from a world that warms by around 4–5°C to one limiting global warming to below 2°C. Whilst there is evidence that this transition is feasible, it will require early action to reduce emissions and to develop the potential for large‐scale deployment of a range of low carbon technologies.